STI in History: The Creation of Government-supported Research Institutes during the Park Chung- hee Era - Moon, Manyong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This paper surveys the historical and political background for the Park Chung-hee era in the emergence and expansion of GRIs in the 1960s and 1970s. There existed different formats of scientific research institutes before KIST. Public and national institutes, universities, and universityaffiliated institutes were in operation, and some industrial actors had their own research organizations. This study investigates how and why GRIs (then a new format of institution) emerged given the historical and material environments. This study focuses on how KIST, an institution that started from a single research institute, could gain so much attention and influence to successfully formulate the entire research pattern of Korea.